The International dimension of education - Kenworthy, Leonard S. (Washington, D.C : Assn. for Supervision and Curriculum Developmentm, 1970)
This small book attempts to delineate in a general way the broad outlines of the international dimension of education. It was written at the request of the commission on internal cooperation in education of the association for supervision and curriculum development as a part of the preparation for its world conference, "In the minds of men: educating the young people of the world," Asilomar, California, March 1970. Readers should bear in mind that this is only one of the several dimensions of school, albeit an increasingly important and much neglected aspect.
I. The World of the foreseeable future -- II. The International community and the need for internationally-minded individuals -- III. The International dimension of our schools: some overall considerations -- IV. The International dimension of elementary (primary) schools -- V. The international dimension of secondary school -- VI. Methods and resources for learning in elementary and secondary schools -- VII. The International dimension of institutions of higher learning -- VIII. The International dimension of teacher education.
Includes bibliographical references.
Keywords: INTERNATIONAL EDUCATION